Case report: Bruton tyrosine kinase inhibitor as therapy for chronic lymphocytic leukemia infiltrating a kidney allograft - Stavart, Louis; Halfon, Matthieu; Dewarrat, Natacha; Rotman, Samuel; Golshayan, Dela (Frontiers in Medicine, 2024)
The burden of chronic lymphocytic leukemia (CLL) in the prognosis of solid organ transplant (SOT) recipients seems non-negligeable. Whether transplanting a patient with previous CLL is safe or what is the optimal monitoring and treatment management after transplantation is still unclear and only based on few case series and reports. Therefore, we aimed to contribute to this understanding by reporting the first documented case of a clinically significant CLL with biopsy-proven infiltration of the kidney allograft and its successful management with a Bruton tyrosine kinase inhibitor (BTKi). We then reviewed the related literature, with a focus on CLL and kidney transplantation. Our main message is that BTKi may represent a safe and effective intervention to prevent the hazardous patient and graft outcomes of CLL in SOT patients.